TEXTUAL METAFUNCTION IN MARTHIN LUTHER SPEECH I HAVE A DREAM - Niat Hati Amazihono; Sahlan Tampubolon; Longe Kuoc Nguyen (Merwin Publisher, 2025)
This research aims to examine the realization of textual metafunction and the kinds of mood and theme that dominate in Martin Luther King's Speech I Have a Dream. This research employed a qualitative research method and content analysis approach. The data were obtained from Martin Luther's speech and analyzed using Halliday's theory, following the steps of data analysis proposed by Bogdan & Biklen. As a result of analysis, it was discovered that: (1) the realization of textual metafunction in Martin Luther's speech was applied which is 268 clauses found in Martin Luther's speech, and each clause contained Theme and Rheme; (2) mood (a theme in declarative clauses) were mostly dominated particularly marked theme which had 125 clauses while unmarked theme 126 clauses. Otherwise, the theme in imperative clauses was not found in Martin Luther's speech. Meanwhile, (theme in interrogative clauses) wh-question; 17 clauses and yes or no was not found, theme types (ideational/topical theme was dominant), it consisted of 128 clauses, the second was (textual theme), it consisted of 113 clauses and the last was (interpersonal theme), it consists 27 clauses. Based on the result, it was expected that the readers employ textual metafunction in their objects since it is greatly effective in delivering the message to the listeners.